The FCS-LIKE ZINC FINGER 6 and 10 are involved in regulating osmotic stress responses in Arabidopsis. (3rd June 2019) - Jamsheer K, Muhammed; Singh, Dhriti; Sharma, Mohan; Sharma, Manvi; Jindal, Sunita; Mannully, Chanchal T.; Shukla, Brihaspati N.; Laxmi, Ashverya
ABSTRACT: The TARGET OF RAPAMYCIN-SNF1-RELATED PROTEIN KINASE 1 (TOR-SnRK1) arms race is a key regulator of plant growth in response to energy fluctuations and stress. Recently, we have identified that two members of the FCS-LIKE ZINC FINGER (FLZ) protein family, FLZ6 and 10, repress SnRK1 signaling and thereby involved in the activation of the TARGET OF RAPAMYCIN (TOR) signaling. In this study, we demonstrate that FLZ6 and 10 are also involved in the regulation of osmotic stress responses. Downregulation of FLZ6 and 10 results in enhanced expression of stress-responsive genes and better resilience towards osmotic stress at the seedling stage. These results indicate that FLZ6 and 10 are involved in the regulation of stress mitigation in plants through directly affecting SnRK1 signaling.